Modifiable lifestyle behaviours impact the health‐related quality of life of bladder cancer survivors - Chung, Jiil (BJU Int, 2020)
OBJECTIVE: To examine health behaviours in bladder cancer survivors including physical activity (PA), body mass index, diet quality, smoking and alcohol consumption, and to explore their relationship with health‐related quality of life (HRQoL). SUBJECTS/PATIENTS AND METHODS: Cross‐sectional questionnaire packages were distributed to bladder cancer survivors (muscle‐invasive bladder cancer [MIBC] and non‐muscle‐invasive bladder cancer [NMIBC]) aged >18 years, and proficient in English. Lifestyle behaviours were measured using established measures/questions, and reported using descriptive statistics. HRQoL was assessed using the validated Bladder Utility Symptom Scale, and its association with lifestyle behaviours was evaluated using analysis of covariance (ancova) and multivariate regression analyses. RESULTS: A total of 586 participants completed the questionnaire (52% response rate). The mean (SD) age was 67.3 (10.2) years, and 68% were male. PA guidelines were met by 20% (n = 117) and 22.7% (n = 133) met dietary guidelines. In all, 60.9% (n = 357) were overweight/obese, and the vast majority met alcohol recommendations (n = 521, 92.5%) and were current non‐smokers (n = 535, 91.0%). Health behaviours did not differ between MIBC and NMIBC, and cancer treatment stages. Sufficient PA, healthy diet, and non‐smoking were significantly associated with HRQoL, and the number of health behaviours participants engaged in was positively associated with HRQoL (P < 0.001). CONCLUSION: Bladder cancer survivors are not meeting guidelines for important lifestyle behaviours that may improve their overall HRQoL. Future research should investigate the impact of behavioural and educational interventions for health behaviours on HRQoL in this population.